The Reception of the Theology of Karl Barth in Scotland - McPake, John L. (Tyndale bulletin, 1996)
A dissertation seeking to challenge the account of the reception of Karl Barth’s theology within Scotland as offered by the leading Scottish theologian Thomas Forsyth Torrance.